Pharmacological and Genetic Inhibition of HDAC4 Alleviates Renal Injury and Fibrosis in Mice - Shen, Fengchen; Hou, Xiying; Li, Tingting; Yu, Jianjun; Chen, Huizhen; Liu, Na; Qiu, Andong; Zhuang, Shougang (Frontiers in Pharmacology, 2022)
Histone deacetylase 4 (HDAC4) has been shown to be involved in cell proliferation, differentiation and migration, and is associated with a variety of cancers. However, the role of HDAC4 in renal fibrogenesis and its mechanisms are unclear. We assessed the role of HDAC4 and possible mechanisms of fibrosis in a murine model of kidney injury induced by unilateral ureteral obstruction (UUO) using tasquinimod, a highly selective HDAC4 inhibitor and knockout mice with depletion of HDAC4 in renal tubular cells. UUO injury resulted in increased expression of HDAC4 and fibrotic proteins fibronectin and α-smooth muscle actin, while treatment with tasquinimod or knockout of HDAC4 significantly reduced their expression. Pharmacological and genetic inhibition of HDAC4 also decreased tubular epithelial cell arrest in the G2/M phase of the cell cycle, expression of transforming growth factor-β1 and phosphorylation of Smad3, signal transducer and activator of transcription 3 and extracellular signal-regulated kinase 1/2 in the injured kidney. Moreover, tasquinimod treatment or HDAC4 deletion inhibited UUO-induced renal tubular cell injury and apoptosis as indicated by reduced expression of neutrophil gelatinase associated lipocalin, Bax and inhibition of caspase-3. Finally, administration of tasquinimod or knockdown of HDAC4 prevented injury-related repression of Klotho, a renoprotective protein. Our results indicate that HDAC4 is critically involved in renal tubular injury and fibrosis and suggest that HDAC4 is a potential therapeutic target for treatment of chronic fibrotic kidney disease.